Dietary Salt (Sodium Chloride) Requirement and Adverse Effects of Salt Restriction in Humans - Nishimuta, Mamoru; Kodama, Naoko; Yoshitake, Yutaka; Shimada, Mieko; Serizawa, Naho (Journal of nutritional science and vitaminology, 2018)
Inevitable sodium loss under sodium restriction must not be construed as evidence for the estimated average requirement (EAR) for sodium (Na) in humans. We conducted human mineral balance studies to determine the EAR for some minerals (Na, K, Ca, Mg, P, Zn, Fe, Cu and Mn). Na concentration in arm sweat was low while those of calcium (Ca) and magnesium (Mg) were high, during relatively heavy bicycle-ergometer exercise under relatively low Na intake (100 mmol/d). This suggests that Na was released from the bone, the sole pool of Na, with Ca and Mg. Additionally, the negative balances of Ca and Mg was observed under a relatively low sodium intake (100 mmol/d) even with the sufficient supply and intake of Ca and Mg into human body. Finally, we found no correlation between the Na intake and the Na balance, while the Na-intake was correlated significantly to the balances of K, Ca and Mg. The Na intake necessary to keep the balances of Ca and Mg positive was calculated to be 68 mg/kg body weight/d. To learn the signs and symptoms of low sodium intake, we compared the results of a metabolic study in which subjects consumed diets with 6 g and 12 g salt/d respectively. The blood pressure decreased only with the 6 g/d group. Fecal moisture contents of the 6 g/d group were lower than for the 12 g/d group, suggesting the fecal Na was strongly reabsorbed with water when the dietary Na was insufficienct. Indiscriminate Na restriction may have adverse effects on health.